The impact of the Alchler model on achieving and developing proactive motivation The female students of the Institute of Fine (Journal of the College of Basic Education, 2024)
The current research aims to identify The impact of the Alchler model on achieving and developing proactive motivation The female students of the Institute of FineArts in Aesthetic education subject. The study relied on the experimental method. The study sample consisted of (30) female students from the Institute of Fine Arts - Al-Karkh First - Design Department from the second grade students. The study tools were the cognitive achievement test, and the proactive motivation scale prepared by (Zizfon 2022), and the study reached the following conclusions:The presence of statistically significant differences at the level of significance (0.05) between the average degree of the sample in the knowledge achievement test and for the benefit of the remote test.The presence of statistically significant differences at the level of significance (0.05) between the average degree of the sample personnel in the motivation scale and in favor of the post -test.The size of the effect was the value of the effect of the effect is equal to (2,15) and it represents the size of a significant effect, and the value of the effect of the effect of the second dependent (motivation) variable (2.75) was also represented by the amount of a significant effect of the independent variable in the dependent variable according to the Cohen classification of the amount of the effect of the effect .The impact of the Traler model for the collection and development of pre -emptive motivation among students of the Institute of Fine Arts in the aesthetic education subject.